2021
DOI: 10.3390/cells10123408
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Central Nervous System Involvement from Epithelial Ovarian Cancer

Abstract: Epithelial ovarian cancer (EOC) is the leading cause of death among women affected by gynaecological malignancies. Most patients show advanced disease at diagnosis (FIGO stage III-IV) and, despite the introduction of new therapeutic options, most women experience relapses. In most cases, recurrence is abdominal-pelvic; however, EOC can occasionally metastasize to distant organs, including the central nervous system. The incidence of brain metastases (BMs) from EOC is low, but it has grown over time; currently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 104 publications
(124 reference statements)
0
6
0
Order By: Relevance
“…sustained delivery of TLZ is the potential for remote metastasis, particularly in the CNS. Brain metastasis in epithelial ovarian cancer is relatively rare, with an incidence of 1.17% ( 66 , 67 ); however, the risk increases threefold to 3.84% ( 19 ) in the presence of BRCA mutations. This highlights the importance of ensuring the systemic efficacy of this i.p.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…sustained delivery of TLZ is the potential for remote metastasis, particularly in the CNS. Brain metastasis in epithelial ovarian cancer is relatively rare, with an incidence of 1.17% ( 66 , 67 ); however, the risk increases threefold to 3.84% ( 19 ) in the presence of BRCA mutations. This highlights the importance of ensuring the systemic efficacy of this i.p.…”
Section: Discussionmentioning
confidence: 99%
“…However, women with pathogenic BRCA1 or BRCA2 mutations have a 55-72% and 45-69% chance of developing ovarian cancer by age 80, respectively ( 13 16 ). Population-based studies have shown that BRCA1 and BRCA2 mutations are found in roughly 15% of all ovarian cancer cases ( 17 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…The study did not demonstrate statistical significance in overall survival between the two groups. In this editorial, we draw attention to a comprehensive review by Scotto et al [ 61 ] featured in the current issue, reviewing the latest literature on biomarkers for the development of BMs in women with EOC.…”
Section: Microtubule-associated-proteins (Maps) and Microtubule Stabi...mentioning
confidence: 99%
“…Hormonal receptors may play a role as therapeutic targets. However, to date, no studies have been reported on hormonal therapy for EOC patients with BM [ 61 ]. Other markers, such as BRCA and multidrug resistance protein (MDR)-1, have been studied [ 58 , 65 , 66 ].…”
Section: Microtubule-associated-proteins (Maps) and Microtubule Stabi...mentioning
confidence: 99%
“…However, data from autopsy studies performed on cancer patients showed a prevalence of solid BMs of up to 40% suggesting that many cases are asymptomatic and undiagnosed ( 6 , 7 ). The most common solid tumors associated with the development of BMs are in order lung, breast, colorectal cancer, and melanoma, while in other tumor types, including gynecological ones, BMs are very rare ( 6 13 ). In this context, the prevalence of BMs from GTN is very low, although variations occurred over the years mainly due to the development of new diagnostic and therapeutic approaches.…”
Section: Epidemiology Of Gtn Brain Metastasismentioning
confidence: 99%